Autonomous driving system and system hacking protection using V2X communication - Rhee, Eugene; Cho, Junhee (Indonesian Journal of Electrical Engineering and Computer Science, 2025)
In this paper, a new autonomous driving system is proposed and problems such as systematic errors that may occur in the autonomous driving system were solved through vehicle to everything (V2X) communication technology. In the actual driving environment, accidents caused by the absence of communication between drivers and communication with infrastructure are frequently exposed. To solve these problems, a system was established that linked V2X communication with a vehicle system. In order to predict and study how this technology works in real traffic situations, it requires a lot of time, manpower, and funds because it requires building an environment similar to real traffic situations and using measuring equipment. For this reason, the system was built with simple model, and the research was conducted through simple simulation. In addition, as network technology and sensing technology for autonomous vehicles develop, the risk of hacking is also increasing. In this paper, various expected attack paths and methods that can hack autonomous vehicles are explained, and methods for defending them are presented.